2020
DOI: 10.5114/hpc.2020.98471
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 on the Physical Activity and Well-Being of Hungarian Athletes and Sports Professionals

Abstract: Authors' contribution Wkład autorów: A. Study design/planning zaplanowanie badań B. Data collection/entry zebranie danych C. Data analysis/statistics dane-analiza i statystyki D. Data interpretation interpretacja danych E. Preparation of manuscript przygotowanie artykułu F. Literature analysis/search wyszukiwanie i analiza literatury G. Funds collection zebranie funduszy Summary Background. The COVID-19 pandemic had a significant effect on regular activities and lifestyles in Hungary in the second quarter of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…In the analysis of the quality of life variables, no significant gender differences were found in the well-being index across sectors based on the self-reported well-being of the respondents. In the study of Szabó et al, athletes and sports sector workers rated their wellbeing index with an average score of 8.41±3.24 [9], which was higher than the representative mean score of 7.67 for Hungarian residents in the study of Ács et al In our study, men with multiple roles rated their well-being with the highest score (8.89), followed by elite male athletes (8.78). Kovács' study suggests that an athlete or a person with a sporting background has higher adaptability and tolerance due to playing sport, as the personality traits of an athlete Health Problems of Civilization ISSN: 2353-6942; eISSN: 2354-0265 make it easier to overcome difficulties [26].…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…In the analysis of the quality of life variables, no significant gender differences were found in the well-being index across sectors based on the self-reported well-being of the respondents. In the study of Szabó et al, athletes and sports sector workers rated their wellbeing index with an average score of 8.41±3.24 [9], which was higher than the representative mean score of 7.67 for Hungarian residents in the study of Ács et al In our study, men with multiple roles rated their well-being with the highest score (8.89), followed by elite male athletes (8.78). Kovács' study suggests that an athlete or a person with a sporting background has higher adaptability and tolerance due to playing sport, as the personality traits of an athlete Health Problems of Civilization ISSN: 2353-6942; eISSN: 2354-0265 make it easier to overcome difficulties [26].…”
Section: Discussioncontrasting
confidence: 74%
“…Ráthonyi's study found that adult workers had decreased physical activity levels and increased sedentary time during lockdowns [12]. Szabó and colleagues also came to a similar conclusion for sportspeople [9]. McCarthy and colleagues found a correlation between physical inactivity and lockdowns [11].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Studies conducted during the COVID-19 pandemic have strengthened the evidence of the positive impact of physical activity on subjective psychological well-being in the significantly changed psychosocial and environmental conditions as well. The subjective psychological well-being of the inactive population and groups with low physical activity was, on average, more unfavorable than those with higher physical activity [15,52,66,72]. According to these studies, the decrease in physical activity impacts subjective psychological well-being negatively and it is independent of the individual's fitness level [15].…”
Section: Sport and Subjective Psychological Well-being In The Covid-1...mentioning
confidence: 97%
“…The restrictions and lockdowns imposed because of the COVID-19 pandemic decreased the opportunities for physical activities and had a negative impact on the sports sector. Several authors have argued about the changes in physical activity, or the impact on the sports industry [63][64][65][66][67]. Some studies, which covered more continents, have concluded that, in the first two phases of the COVID-19 pandemic, the physical activity of the population decreased almost everywhere and sitting activities increased [64,68].…”
Section: Sport and Subjective Psychological Well-being In The Covid-1...mentioning
confidence: 99%